A novel chiral electrochemiluminescence sensor that can discriminate proline enantiomers. Issue 114 (3rd November 2015) - Wang, Qinghong; Lin, Xia; Guo, Dongmei; Xu, Juanjuan; Xuan, Chunzhi; Chen, Cui; Fu, Yingzi
Abstract : A chiral stereoselective electrochemiluminescence (ECL) sensor was constructed by using Ru–AuNPs and β-CD–rGO composites to discriminate proline enantiomers. Abstract : A sensitive, stable and stereoselective electrochemiluminescence (ECL) sensor has been designed to enantioselectively discriminate proline enantiomers by immobilizing Ru(bpy)3 2+ –gold nanoparticles (Ru–AuNPs) and β-cyclodextrin–reduced graphene oxide (β-CD–rGO) on glassy carbon electrode. More Ru(bpy)3 2+ could be immobilized on the surface of electrode stably via preparing Ru–AuNPs and better stereoselectivity could be introduced to the sensor via the synthesis of β-CD–rGO. When the developed sensor interacted with proline enantiomers, obvious difference of ECL intensities towardsl - andd -proline was observed, and a larger intensity was obtained fromd -proline. As a result, ECL technique might act as a promising method to chiral recognition of amino acids enantiomers or chiral drugs.